Sustainable Tourism in Reykjavik - Stoyanov, Encho Plamenov, 1988- (2012)
Abstract For the past few years‟ sustainability has become a buzzword in modern societies. Nowadays many people, organizations and companies try to be friendlier to the environment, to live in a more sustainable way and to pollute the environment less. This paper reviews some of the major actors for sustainable tourism analyses. The actors are namely: local tourism enterprises & tour operators, host population (locals) & tourists, tourist authorities (national tourism organizations, governments etc.), nongovernmental organisations (NGO‟s), and environmental organisations. The accent of the essay is upon the host population and the tourists for the objective of this essay is to find out whether tourists and citizens of Reykjavik are familiar with the concept of sustainable tourism. The objectives were also to introduce to the reader the concepts of sustainable development and sustainable tourism, to present what has been done in Iceland on the matter, as well as the attitude of local people and tourist towards those topics. A questionnaire survey was created and spread out among tourists and citizens of Reykjavik. The survey was organised in the manner of the structured questionnaire with a few open questions. Primary data was selected by distribution of the semistructured questionnaires. In total 552 people participated in the research – 452 citizens of Reykjavik and 100 tourists visiting the capital. The main outcome of the research is that the meaning of the word „sustainability‟ and concepts such as „sustainable tourism‟ and „sustainable development‟ are unclear for most people, regardless of their background and place in society. Most of the citizens of Reykjavik do not feel responsibility towards the image of the tourism industry, while most tourists feel that they have responsibility towards the city of Reykjavik, yet the citizens of Reykjavik are for the further developing of the tourism industry and both groups claim that tourism is beneficial for the Icelandic capital. Keywords: sustainability, ...